2002
DOI: 10.1055/s-2002-23130
|View full text |Cite
|
Sign up to set email alerts
|

Platycodin D and D3 Increase Airway Mucin Release in vivo and in vitro in Rats and Hamsters

Abstract: The root of Platycodon grandiflorum has been widely used for the treatment of various chronic inflammatory diseases including airway disease in oriental medicine. The root extract of the plant has been known to be effective in the expectoration of sputum or mucus, thereby improving airway respiratory function and preventing secondary airway inflammation. In this study, we investigated the effect of platycodin D and D3, the saponin components that are anti-inflammatory components in Platycodon grandiflorum. Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 17 publications
4
38
0
1
Order By: Relevance
“…1 Although many compounds have been isolated from P. grandiflorum roots, PD has shown the most potent biological activities of all the platycodin saponins. [2][3][4][5][6][7] Recent studies have shown that PD effectively induces apoptosis in many cancer cells; 8,9 however, the underlying cellular and molecular mechanisms responsible for PD's anticancer activity in human leukemia cells are not known. In our study, we first provided the apoptotic mechanisms induced by PD in leukemia cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Although many compounds have been isolated from P. grandiflorum roots, PD has shown the most potent biological activities of all the platycodin saponins. [2][3][4][5][6][7] Recent studies have shown that PD effectively induces apoptosis in many cancer cells; 8,9 however, the underlying cellular and molecular mechanisms responsible for PD's anticancer activity in human leukemia cells are not known. In our study, we first provided the apoptotic mechanisms induced by PD in leukemia cells.…”
Section: Discussionmentioning
confidence: 99%
“…PD contains a crucial bioactive component responsible for diverse effects such as anti-inflammatory, antiallergic and cholesterol-lowering activities. [3][4][5][6][7] Although recent studies have also shown that PD can induce apoptosis in several cancer cells, 8,9 until now no clear or unique mechanisms of PD-induced apoptosis are known.…”
mentioning
confidence: 99%
“…19) Saponins (PS) are the primary constituents of Platycodi Radix, [20][21][22] and they are responsible for diverse effects including anti-inflammation, [23][24][25][26] anti-allergy, 23) anti-tumor, 27) augmentation of immune response, [28][29][30] and stimulating the apoptosis in skin cells. 27) In the last decade, PS has generated renewed interests due to their pharmacological potentials for healing the diseases of adulthood such as hyperlipidemia or anti-obesity.…”
Section: )mentioning
confidence: 99%
“…In Korea, people usually gather bellflower roots in spring and autumn to use in seasoned salads or as a cooked potherb. In addition, because it is known to have a mucolytic and antitussive effect, Campanula punctata is used in Oriental medicine for the treatment of acute or chronic bronchitis, tonsillitis, and asthma [2].…”
Section: Introductionmentioning
confidence: 99%